A dual functional liposome specifically targets melanoma cells through integrin and ephrin receptors. Issue 114 (2nd December 2016) - Bhunia, Debmalya; Saha, Abhijit; Adak, Anindyasundar; Das, Gaurav; Ghosh, Surajit
Abstract : A novel bi-functional liposome delivers docetaxel specifically to melanoma cancer cells targeting integrin (α4 β1 ) and ephrin (EphA2) receptors and enhances the efficacy of docetaxel. Abstract : A novel bi-functional liposome is designed using two novel lipo peptides, which delivers docetaxel specifically to melanoma cell targeting integrin (α4 β1 ) and ephrin (EphA2) receptors and enhances efficacy of docetaxel in melanoma cells.